Low vitamin D serum level is related to severe fibrosis and low responsiveness to interferon‐based therapy in genotype 1 chronic hepatitis C - Petta, Salvatore; Cammà, Calogero; Scazzone, Concetta; Tripodo, Claudio; Di Marco, Vito; Bono, Antonino; Cabibi, Daniela; Licata, Giusalba; Porcasi, Rossana; Marchesini, Giulio; Craxí, Antonio (Hepatology (Baltimore, Md.), 2010)
25‐Hydroxyvitamin D (25[OH]D) can potentially interfere with inflammatory response and fibrogenesis. Its role in disease progression in chronic hepatitis C (CHC) and its relation with histological and sustained virological response (SVR) to therapy are unknown. One hundred ninety‐seven patients with biopsy‐proven genotype 1 (G1) CHC and 49 healthy subjects matched by age and sex were consecutively evaluated. One hundred sixty‐seven patients underwent antiviral therapy with pegylated interferon plus ribavirin. The 25(OH)D serum levels were measured by high‐pressure liquid chromatography. Tissue expression of cytochrome (CY) P27A1 and CYP2R1, liver 25‐hydroxylating enzymes, were assessed by immunochemistry in 34 patients with CHC, and in eight controls. The 25(OH)D serum levels were significantly lower in CHC than in controls (25.07 ± 9.92 μg/L versus 43.06 ± 10.19; P < 0.001). Lower levels of 25(OH)D were independently linked to female sex (P = 0.007) and necroinflammation (P = 0.04) by linear regression analysis. CYP27A1, but not CYP2R1, was directly related to 25(OH)D levels (P = 0.01), and inversely to necroinflammation (P = 0.01). Low 25(OH)D (odds ratio [OR], 0.942; 95% confidence interval [CI], 0.893–0.994) and cholesterol (OR, 0.981; 95%CI, 0.969–0.992) levels, older age (OR, 1.043; 95%CI, 1.002–1.085), high ferritin (OR, 1.003; 95%CI, 1.001–1.005), and necroinflammation (OR, 2.235; 95%CI, 1.014–4.929) were independently associated with severe fibrosis (F3–F4) by multivariate logistic analysis. Seventy patients (41%) achieved SVR. By multivariate analysis, hepatic steatosis (OR, 0.971; 95%CI, 0.944–0.999), lower cholesterol (OR, 1.009; 95% CI, 1.000–1.018), and 25(OH)D levels (OR, 1.039; 95%CI, 1.002–1.077) were independently associated with no SVR. Conclusion: G1 CHC patients had low 25(OH)D serum levels, possibly because of reduced CYP27A1 expression. Low vitamin D is linked to severe fibrosis and low SVR on interferon (IFN)‐based therapy. (HEPATOLOGY 2010.)